2016
DOI: 10.1074/jbc.m116.747527
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of a Ruminal β-Glycosidase Defines a Novel Subfamily of Glycoside Hydrolase Family 3 with Permuted Domain Topology

Abstract: Metagenomics has opened up a vast pool of genes for putative, yet uncharacterized, enzymes. It widens our knowledge on the enzyme diversity world and discloses new families for which a clear classification is still needed, as is exemplified by glycoside hydrolase family-3 (GH3) proteins. Herein, we describe a GH3 enzyme (GlyA1) from resident microbial communities in strained ruminal fluid. The enzyme is a β-glucosidase/β-xylosidase that also shows β-galactosidase, β-fucosidase, α-arabinofuranosidase, and α-ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
0
13
0
1
Order By: Relevance
“…These reactions can happen between two carbohydrates or between a carbohydrate and a noncarbohydrate moiety (amino acids, e.g., in glycoproteins) . Due to the critical role of carbohydrates in human health as well as their possible use as fuel, there has been an increased interest in the study of glycosidases in recent years …”
Section: Introductionmentioning
confidence: 99%
“…These reactions can happen between two carbohydrates or between a carbohydrate and a noncarbohydrate moiety (amino acids, e.g., in glycoproteins) . Due to the critical role of carbohydrates in human health as well as their possible use as fuel, there has been an increased interest in the study of glycosidases in recent years …”
Section: Introductionmentioning
confidence: 99%
“…Five glycosidases from the GH3 (PDB 3U48 and 5K6M), GH9 (PDB 1JS4 and 3X17), and GH116 (PDB 5BX5) families that shared the highest similarity to Bgl1D were selected for the alignment (Table S5). Blast results showed that Bgl1D shared approximately 16.57%, 27.49%, 24.56%, 20.78%, and 26.67% identities with the amino acids of 3U48, 5K6M [39], 1JS4 [40], 3X17 [41], and 5BX5 [42], respectively. A comparison of the amino acid of Bgl1D with these β-glucosidases demonstrated that the Asp44 of Bgl1D was similar to 3U48 (GH3 family) and 1JS4 (GH9 family) whose residue Asp was generally used as conserved catalytic nucleophile base or catalytic proton donor according to the information of β-glucosidase (EC 3.2.1.21) from the CAZy database (http://www.cazy.org) ( Figure 3) [43].…”
Section: Discussionmentioning
confidence: 99%
“…The alignment of the GspInv amino acid sequence with other characterized invertases revealed the GspInv contains conserved motifs of GH32 invertases (Supplementary Figure S1). Based on their alignments, residues D46, D173, and E251 of GspInv were identified as the nucleophile, transitionstate stabilizer, and general acid/base catalyst, respectively (Supplementary Figure S1; Pons et al, 2004;Ramírez-Escudero et al, 2016). Trollope et al (2015) reported that GH32 invertases can be divided into two groups, including that with lowand high-level fructooligosaccharide synthesis abilities based on the conserved motifs unique to each group.…”
Section: Gspinv Cloning and Sequence Analysismentioning
confidence: 99%